SEISMIC STRATIGRAPHY ANALYSIS OF 2D SEISMIC CROSS SECTION IN ARAFURA SEA, PAPUA - Naufal, Muhammad Audy; Nurdrajat, Nurdrajat; Muljana, Budi; Purwanto, Catur (Journal of Geological Sciences and Applied Geology, 2021)
Arafura Sea is one of the shallow marine located in eastern Indonesia. This is accommodated based on the bathymetry map of Arafura which has a depth of up to 90 meters. Stratigraphy in eastern Indonesia is quite complex, consisting of rocks aged up to Paleozoic. There have been five tectonic event since Pre-Cambrian until now, namely the pre-rift, syn-rift, passive margins, convergence and compression. The 2D seismic  cross section of line 5 acquired as the result of seismic data processing which is part of the Buru Formation consisting of shale siltstone, sandstone, limestone, calcareous sandstone aged from Late Miocene to Plio-Pleistocene. Bouguer Anomaly data from Buru Formation have a value of 1,8 – 2,2 gr /cc which shows fine grained sediments in the form of silt, clay, and sand which deposited on the continental shelf. 2D Seismic cross section of line 5 shows the direction of sediment deposition obtained from the south which continues to fill the geometry of the basin in the north and divided into 4 seismic facies based on the characteristics of the internal reflector, amplitude, frequency and continuity. From these characteristics, there is a process of changing depositional energy that tends to slow toward the center of the geometry space of the depositional basin so that the resulting sedimentation pattern is uniformed. A fault structure has been identified  which is formed the compressional force due to the presence of convergent tectonics which is perpendicular to the direction of the bedding